Increasing access to specialty care: A pilot, randomized controlled trial of telemedicine for Parkinson's disease - Dorsey, E. Ray; Deuel, Lisa M.; Voss, Tiffini S.; Finnigan, Kara; George, Benjamin P.; Eason, Sheelah; Miller, David; Reminick, Jason I.; Appler, Anna; Polanowicz, Joyce; Viti, Lucy; Smith, Sandy; et al. (Movement disorders, 2010)
We conducted a randomized, controlled pilot trial to evaluate the feasibility of providing subspecialty care via telemedicine for patients with Parkinson's disease residing in a remote community located ∼130 miles from an academic movement disorders clinic. Study participants were randomized to receive telemedicine care with a movement disorder specialist at the University of Rochester or to receive their usual care. Participants in the telemedicine group received three telemedicine visits over six months. Feasibility, as measured by the completion of telemedicine visits, was the primary outcome measure. Secondary measures were quality of life, patient satisfaction, and clinical outcomes. Ten participants residing in the community were randomized to receive telemedicine care (n = 6) or their usual care (n = 4). Four nursing home patients were assigned to telemedicine. Those receiving telemedicine completed 97% (29 of 30) of their telemedicine visits as scheduled. At the study's conclusion, 13 of 14 study participants opted to receive specialty care via telemedicine. Compared with usual care, those randomized to telemedicine had significant improvements in quality of life (3.4 point improvement vs. 10.3 point worsening on the Parkinson's Disease Questionnaire 39; P = 0.04) and motor performance (0.3 point improvement vs. 6.5 point worsening on the Unified Parkinson's Disease Rating Scale, motor subscale; P = 0.03). Relative to baseline, nursing home patients experienced trends toward improvement in quality of life and patient satisfaction. Providing subspecialty care via telemedicine for individuals with Parkinson's disease living remotely is feasible. © 2010 Movement Disorder Society